PENGARUH MEDIA APLIKASI CANVA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS XI PERHOTELAN SMK NEGERI 6 SEMARANG - Septia Nurul Hapsari; Supandi Hadiwiyono; Pramono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the effect of using Canva application media on learning motivation of class XI hospitality students of SMK Negeri 6 Semarang. The method used is quantitative research with the help of SPSS (Statistical Product and Service Solution). Simple linear regression analysis was conducted to test the correlation and impact of using Canva on learning motivation. The results of the analysis showed a significant positive correlation between the use of Canva and students' learning motivation (Sig. <0.05). The coefficient of determination of 0.558 indicates that about 55.8% of the variation in learning motivation can be explained by Canva media application while the other 44.2% is explained by other variables. This finding confirms that Canva app media has a relevant impact on learners' learning motivation. Thus, this study concludes that the use of Canva app media has the potential to increase the learning motivation of XI hospitality learners of SMK Negeri 6 Semarang and it is important for educators to consider this factor in designing learning experiences that motivate and support learners' development in the classroom.